2020
DOI: 10.5433/1679-0367.2020v41n2p217
|View full text |Cite
|
Sign up to set email alerts
|

O processo de amamentação do bebê pré-termo: perspectiva dos registros maternos no “diário do bebê

Abstract: Objetivo: Descrever os fatores envolvidos no processo de amamentação do bebê pré-termo internado em uma Unidade Neonatal registrados em um “Diário do bebê” preenchido pela mãe. Método: Pesquisa descritiva, prospectiva e longitudinal, com abordagem quantitativa, realizada no período de setembro de 2010 a junho de 2011 com 38 mães de recém-nascidos pré-termo internados na Unidade Neonatal. Resultados: Predomínio de mães com idade entre 20 a 34 anos, com companheiro, escolaridade maior de oito anos, renda familia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…In addition, support from family and health professionals was significantly associated with initiation of breastfeeding and duration of exclusive breastfeeding. Despite the long-term adoption of WHO recommendations for breastfeeding in the UAE, rates remain suboptimal [21] and these results are similar to the findings of AIRES et al [22], where it was found that women who have partners tend to be more successful in breastfeeding, compared to single mothers. Education also has an influence on breastfeeding, since women with complete high school and/or higher education are successful in breastfeeding and are more likely to not abandon the lactation process.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, support from family and health professionals was significantly associated with initiation of breastfeeding and duration of exclusive breastfeeding. Despite the long-term adoption of WHO recommendations for breastfeeding in the UAE, rates remain suboptimal [21] and these results are similar to the findings of AIRES et al [22], where it was found that women who have partners tend to be more successful in breastfeeding, compared to single mothers. Education also has an influence on breastfeeding, since women with complete high school and/or higher education are successful in breastfeeding and are more likely to not abandon the lactation process.…”
Section: Discussionsupporting
confidence: 85%